Visceral obesity relates to deep white matter hyperintensities via inflammation. Issue 2 (29th January 2019) - Lampe, Leonie; Zhang, Rui; Beyer, Frauke; Huhn, Sebastian; Kharabian Masouleh, Shahrzad; Preusser, Sven; Bazin, Pierre‐Louis; Schroeter, Matthias L.; Villringer, Arno; Witte, A. Veronica
Abstract : Objective: White matter hyperintensities (WMHs) are linked to vascular risk factors and increase the risk of cognitive decline, dementia, and stroke. We here aimed to determine whether obesity contributes to regional WMHs using a whole‐brain approach in a well‐characterized population‐based cohort. Methods: Waist‐to‐hip ratio (WHR), body mass index (BMI), systolic/diastolic blood pressure, hypertension, diabetes and smoking status, blood glucose and inflammatory markers, as well as distribution of WMH were assessed in 1, 825 participants of the LIFE‐adult study (age, 20–82 years; BMI, 18.4–55.4 kg/m 2 ) using high‐resolution 3‐Tesla magnetic resonance imaging. Voxel‐wise analyses tested if obesity predicts regional probability of WMH. Additionally, mediation effects of high‐sensitive C‐reactive protein and interleukin‐6 (IL6) measured in blood were related to obesity and WMH using linear regression and structural equation models. Results: WHR related to higher WMH probability predominantly in the deep white matter, even after adjusting for effects of age, sex, and systolic blood pressure (mean ß = 0.0043 [0.0008 SE], 95% confidence interval, [0.00427, 0.0043]; threshold‐free cluster enhancement, family‐wise error‐corrected p < 0.05). Conversely, higher systolic blood pressure was associated with WMH in periventricular white matter regions. Mediation analyses indicated that both higher WHR and higher BMI contributed to increased deep‐to‐periventricular WMH ratio through elevated IL6. Interpretation: Our results indicate an increased WMH burden selectively in the deep white matter in obese subjects with high visceral fat accumulation, independent of common obesity comorbidities such as hypertension. Mediation analyses proposed that visceral obesity contributes to deep white matter lesions through increases in proinflammatory cytokines, suggesting a pathomechanistic link. Longitudinal studies need to confirm this hypothesis.ANN NEUROL 2019;85:194–203.